Inhibition of Spinal Ca2+-Permeable AMPA Receptors with Dicationic Compounds Alleviates Persistent Inflammatory Pain without Adverse Effects - Kopach, Olga; Krotov, Volodymyr; Goncharenko, Julia; Voitenko, Nana (Frontiers in Cellular Neuroscience, 2016)
Upregulation of Ca2+-permeable AMPA receptors (CP-AMPARs) in the dorsal horn neurons of the spinal cord has been causally linked to the maintenance of persistent inflammatory pain. Therefore, inhibition of CP-AMPARs could potentially alleviate an, otherwise, poorly treatable chronic pain. However, a loss of CP-AMPARs could produce considerable side effects because of the crucial role of CP-AMPARs in synaptic plasticity. Here we have tested whether the inhibition of spinal CP-AMPARs with dicationic compounds, the open-channel antagonists acting in an activity-dependent manner, can relieve inflammatory pain without adverse effects being developed. Dicationic compounds, N1-(1-phenylcyclohexyl)pentane-1,5-diaminium bromide (IEM-1925) and 1-trimethylammonio-5-1-adamantane-methyl-ammoniopentane dibromide (IEM-1460) were applied intrathecally as a post-treatment for inflammatory pain in the model of complete Freund's adjuvant (CFA)-induced long-lasting peripheral inflammation. The capability of dicationic compounds to ameliorate inflammatory pain was tested in rats in vivo using the Hargreaves, the von Frey and the open-field tests. Treatment with IEM-1460 or IEM-1925 resulted in profound alleviation of inflammatory pain. The pain relief appeared shortly after compound administration. The effects were concentration-dependent, displaying a high potency of dicationic compounds for alleviation of inflammatory hyperalgesia in the micromolar range, for both acute and long-lasting responses. The period of pain maintenance was shortened following treatment. Treatment with IEM-1460 or IEM-1925 changed neither thermal and mechanical basal sensitivities nor animal locomotion, suggesting that inhibition of CP-AMPARs with dicationic compounds does not give rise to detectable side effects. Thus, the ability of dicationic compounds to alleviate persistent inflammatory pain may provide new routes in the treatment of chronic pain.